Terumo spectra optia leukapheresis of cynomolgus macaques for hematopoietic stem cell and T cell collection. Issue 1 (17th September 2020) - Wu, Helen L.; Greene, Justin M.; Swanson, Tonya; Shriver‐Munsch, Christine; Armantrout, Kimberly; Weber, Whitney C.; Bateman, Katherine B.; Maier, Nicholas M.; Northrup, Mina; Legasse, Alfred W.; Moats, Cassandra; Axthelm, Michael K.; et al.
Abstract: Macaques are physiologically relevant animal models of human immunology and infectious disease that have provided key insights and advanced clinical treatment in transplantation, vaccinology, and HIV/AIDS. However, the small size of macaques is a stumbling block for studies requiring large numbers of cells, such as hematopoietic stem cells (HSCs) for transplantation, antigen‐specific lymphocytes for in‐depth immunological analysis, and latently‐infected CD4+ T‐cells for HIV cure studies. Here, we provide a detailed protocol for collection of large numbers of HSCs and T‐cells from cynomolgus macaques as small as 3 kg using the Terumo Spectra Optia apheresis system, yielding an average of 5.0 × 10 9 total nucleated cells from mobilized animals and 1.2 × 10 9 total nucleated cells from nonmobilized animals per procedure. This report provides sufficient detail to adapt this apheresis technique at other institutions, which will facilitate more efficient and detailed analysis of HSCs and their progeny blood cells.